2010
DOI: 10.1104/pp.110.158220
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Components Regulate Entry and Affect Exit of Seasonal Dormancy as Well as Winter Hardiness in Populus Trees    

Abstract: This study addresses the role of the circadian clock in the seasonal growth cycle of trees: growth cessation, bud set, freezing tolerance, and bud burst. Populus tremula 3 Populus tremuloides (Ptt) LATE ELONGATED HYPOCOTYL1 (PttLHY1), PttLHY2, and TIMING OF CAB EXPRESSION1 constitute regulatory clock components because down-regulation by RNA interference of these genes leads to altered phase and period of clock-controlled gene expression as compared to the wild type. Also, both RNA interference lines show abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 42 publications
(60 reference statements)
8
147
0
Order By: Relevance
“…1a). A well-marked oscillatory pattern was detected for PtaLHY2 mRNA accumulation showing a peak at dawn, similarly to the diurnal expression reported for its poplar homologs PnLHY2 and PttLHY2 , and for Arabidopsis LHY [10, 82, 83].
Fig.
…”
Section: Resultssupporting
confidence: 79%
“…1a). A well-marked oscillatory pattern was detected for PtaLHY2 mRNA accumulation showing a peak at dawn, similarly to the diurnal expression reported for its poplar homologs PnLHY2 and PttLHY2 , and for Arabidopsis LHY [10, 82, 83].
Fig.
…”
Section: Resultssupporting
confidence: 79%
“…In Arabidopsis, core clock components CCA1 and LHY regulate expression of the CBF (C-REPEAT BINDING FACTOR) pathway, which is highly conserved among plants and has a major role in plant freezing tolerance [74]. Reducing the expression of LHY genes by RNA interference compromises freezing tolerance in Populus trees [16]. The expression of clock genes may be influenced by seasonal environmental changes, and consequently, may lead to activation of downstream pathways that contribute to freezing tolerance, which is important for survival of tree species in winter.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome dynamics plays important roles for diurnal and seasonal adaptation in plants to synchronize them with environmental changes, and may be under clock control [15][16][17]. Signal transduction mechanisms due to changes in light are well studied in the model angiosperm Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CBF genes has been shown to be gated by a circadian clock (Fowler et al 2005), and more recently Ibañez et al (2010) have shown that genes that constitute regulatory clock components in poplar (PttLHY1, PttLHY2) play a significant role in both the daylength-controlled and temperature-dependent processes of dormancy, cold hardiness, and bud burst, including the expression of poplar CBF1. These observations indicate that genes regulating dormancy and those that regulate cold hardiness may be more interactive than previously expected, especially in woody plants.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal regulation of growth and freezing tolerance is marked by phenological events such as growth cessation, bud set, the onset of dormancy, cold acclimation, deacclimation, and bud burst (Ibañez et al 2010;Kalberer et al 2006). Cold acclimation results in and is governed by a distinct set of changes in gene expression (Chinnusamy et al 2006;Welling and Palva 2006;Thomashow et al 2001).…”
Section: Introductionmentioning
confidence: 99%